2020
DOI: 10.3389/fnsys.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

Neural Working Memory Changes During a Spaceflight Analog With Elevated Carbon Dioxide: A Pilot Study

Abstract: Spaceflight missions to the International Space Station (ISS) expose astronauts to microgravity, radiation, isolation, and elevated carbon dioxide (CO 2), among other factors. Head down tilt bed rest (HDBR) is an Earth-based analog for spaceflight used to study body unloading, fluid shifts, and other factors unrelated to gravitational changes. While in space, astronauts need to use mental rotation strategies to facilitate their adaptation to the ISS environment. Therefore, spatial working memory is essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 52 publications
3
45
1
Order By: Relevance
“…Here, we did not observe any brainbehavior change correlations, complicating interpretations. In this same cohort, we found evidence for both neural compensation and dysfunction as a result of HDBR+CO 2 when participants performed a spatial working memory task (Salazar et al, 2020) or received vestibular stimulation (Hupfeld et al, 2019). However, the lack of associations found in the present study does not allow us to fully interpret whether identified longitudinal neural changes that occur during visuomotor adaptation across HDBR+CO 2 are compensatory or dysfunctional.…”
Section: Brain-behavior Correlationscontrasting
confidence: 80%
See 2 more Smart Citations
“…Here, we did not observe any brainbehavior change correlations, complicating interpretations. In this same cohort, we found evidence for both neural compensation and dysfunction as a result of HDBR+CO 2 when participants performed a spatial working memory task (Salazar et al, 2020) or received vestibular stimulation (Hupfeld et al, 2019). However, the lack of associations found in the present study does not allow us to fully interpret whether identified longitudinal neural changes that occur during visuomotor adaptation across HDBR+CO 2 are compensatory or dysfunctional.…”
Section: Brain-behavior Correlationscontrasting
confidence: 80%
“…Both spaceflight and HDBR are associated with sensory reweighting, changes in cognitive/sensorimotor processes (Bock et al, 2010;Yuan et al, 2016Yuan et al, , 2018Hupfeld et al, 2019), and modifications of brain structure (e.g., Koppelmans et al, 2017;Roberts et al, 2017;Lee et al, 2019b;Hupfeld et al, 2020) and function (Pechenkova et al, 2019) in healthy individuals. Our group (Hupfeld et al, 2019;Lee et al, 2019a;Salazar et al, 2020;McGregor et al, 2021) and others (Zwart et al, 2019;Laurie et al, 2020;Basner et al, 2021) have reported findings from an analog NASA campaign combining HDBR with elevated CO 2 levels. Compared to HDBR alone, elevated CO 2 better mimics the ISS environment (∼0.4% CO 2 ), which has average atmospheric CO 2 levels approximately 10 times greater than those on Earth.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study of HDBR in an elevated CO 2 atmosphere demonstrated altered activation of the brain during vestibular stimulation than during HDBR alone, indicating that increased CO 2 may alter vestibular processing and compensation 44 . HDBR with CO 2 has also been associated with greater decreases in activation of the left inferior temporal gyrus and right hippocampus compared to HDBR alone, regions that are involved in visual memory, cognition and spatial working memory 46 . Fascinatingly, a recent fMRI study demonstrated increased functional connectivity between visual, vestibular and motor brain regions during HDBR with CO 2 ; while decreases in functional connectivity were seen between somatosensory, cognitive, motor, vestibular and multimodal integration regions 45 .…”
Section: Comparison Of Spaceflight-related Cns Alterations To Those Smentioning
confidence: 93%
“…Several recent studies have also explored HDBR with CO 2 as an enhanced model for sensorimotor re-weighting during spaceflight [44][45][46] . A recent study of HDBR in an elevated CO 2 atmosphere demonstrated altered activation of the brain during vestibular stimulation than during HDBR alone, indicating that increased CO 2 may alter vestibular processing and compensation 44 .…”
Section: Comparison Of Spaceflight-related Cns Alterations To Those Smentioning
confidence: 99%